Adaptation to high zinc depends on distinct mechanisms in metallicolous populations of Arabidopsis halleri. Issue 1 (2nd January 2018) - Schvartzman, M. Sol; Corso, Massimiliano; Fataftah, Nazeer; Scheepers, Maxime; Nouet, Cécile; Bosman, Bernard; Carnol, Monique; Motte, Patrick; Verbruggen, Nathalie; Hanikenne, Marc
Summary: Zinc (Zn) hyperaccumulation and hypertolerance are highly variable traits in Arabidopsis halleri . Metallicolous populations have evolved from nearby nonmetallicolous populations in multiple independent adaptation events. To determine whether these events resulted in similar or divergent adaptive strategies to high soil Zn concentrations, we compared two A. halleri metallicolous populations from distant genetic units in Europe (Poland (PL22) and Italy (I16)). The ionomic (Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP‐AES)) and transcriptomic (RNA sequencing (RNA‐Seq)) responses to growth at 5 and 150 μM Zn were analyzed in root and shoot tissues to examine the contribution of the geographic origin and treatment to variation among populations. These analyses were enabled by the generation of a reference A. halleri transcriptome assembly. The genetic unit accounted for the largest variation in the gene expression profile, whereas the two populations had contrasting Zn accumulation phenotypes and shared little common response to the Zn treatment. The PL22 population displayed an iron deficiency response at high Zn in roots and shoots, which may account for higher Zn accumulation. By contrast, I16, originating from a highly Zn‐contaminated soil, strongly responded to control conditions. Our data suggest that distinct mechanisms support adaptation to high Zn in soils among A. halleri metallicolous populations.